Cholesterol Levels in HIV- and/or HCV-Infected Drug Users Living in Argentina. (September 2016) - Kohli, Rakhi; Winston, Diana; Sheehan, Heidi; Muzzio, Estela; Benetucci, Jorge; Weissenbacher, Mercedes; Wanke, Christine; Knox, Tamsin; Tang, Alice
Improved understanding of cholesterol levels in HIV- and hepatitis C virus (HCV)-infected persons in Argentina will guide optimal antiretroviral therapy. The authors conducted a cross-sectional study in Argentina to describe associations between HIV, HCV, and cholesterol. Of the 202 participants, 21 were HIV infected, 15 were HCV infected, 46 were HIV/HCV coinfected, and 120 were HIV/HCV uninfected. HIV/HCV-uninfected participants had the highest total cholesterol (TC) and low-density lipoprotein (LDL) levels. Multivariate modeling revealed that HIV/HCV-coinfected patients had the lowest TC levels (−28.7 mg/dL, P < .001) compared to the HIV/HCV-uninfected reference group. Hepatitis C virus and HIV/HCV coinfection were associated with lower LDL levels (−21.4 mg/dL, P = .001 and −20.3 mg/dL, P < .0001, respectively). HIV and HIV/HCV coinfection, but not HCV alone, were associated with lower high-density lipoprotein levels (−9.1 mg/dL, P = .0008 and −6.8 mg/dL, P = .0006, respectively). Further study is needed to examine whether the more favorable lipid profile observed in HIV/HCV-coinfected persons is associated with a reduction in cardiovascular risk.